2015
DOI: 10.1149/2.0951506jes
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of Conductive Carbon and Ethylene Carbonate in High-Voltage Li-Ion Batteries Quantified by On-Line Electrochemical Mass Spectrometry

Abstract: The anodic oxidation stability of battery components like the conductive carbon black (Super C65) and the co-solvent ethylene carbonate (EC) is of great relevance, especially with regards to high-voltage cathode materials. In this study, we use On-line Electrochemical Mass Spectrometry (OEMS) to deconvolute the CO and CO 2 evolution from the anodic oxidation of carbon and electrolyte by using a fully 13 C-isotope labeled electrolyte based on ethylene carbonate with 2 M LiClO 4 . We present a newly developed tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
276
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(296 citation statements)
references
References 58 publications
(195 reference statements)
16
276
2
2
Order By: Relevance
“…However, as was discussed previously, 24 additional interfacial resistance roughly doubles the overall electrode polarization.…”
Section: On-line Electrochemical Mass Spectrometry (Oems)-supporting
confidence: 54%
See 3 more Smart Citations
“…However, as was discussed previously, 24 additional interfacial resistance roughly doubles the overall electrode polarization.…”
Section: On-line Electrochemical Mass Spectrometry (Oems)-supporting
confidence: 54%
“…This allows electrolyte access and gas diffusion from both sides of the graphite electrode, which is a prerequisite for measurements with the OEMS system. 23,24 Afterwards, the coating was dried overnight in ambient atmosphere on a hot plate held at 60…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[51][52][53] These various studies suggest that the oxidation of electrolyte is a major issue that increases significantly with cell voltage. Self et al recently noted that decomposition products from a sulfur-containing additive (prop-1-ene-1,3-sultone) and the organic carbonate solvent oxidation have been observed at lower electrode potentials (i.e., ∼4.2 -4.7 V vs. Li/Li + ) 42 than expected from voltammetric studies (>5.3 V vs. Li/Li + ) [54][55][56][57][58] and density functional theory (DFT) calculations (> 6.0 V vs. Li/Li + ). 56,59 However it is noted that there is not universal agreement for the onset potential for electrochemical oxidation of organic carbonates (e.g., Moshkovich et al reported oxidation at > 3.9 V vs. Li/Li + ).…”
mentioning
confidence: 99%